2017
DOI: 10.3892/ijmm.2017.3063
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of yellow catfish protein hydrolysate on mice fed a 45% kcal high-fat diet

Abstract: Obesity contributes to the etiologies of a variety of comorbid conditions, such as type 2 diabetes, hypertension and cardiovascular disease. In the present study, the anti-obesity effects of yellow catfish protein hydrolysate (YPh) were observed in mice fed a 45% kcal high-fat diet (HFD) compared with those of mice treated with simvastatin. The HFD-fed control mice exhibited noticeable increase in body weight, and whole-body and abdominal fat densities, periovarian and abdominal wall-deposited fat pad weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Our results are in agreement with Kim et al. that showed that protein hydrolysate reduces the oxidative stress in vivo and increase the antioxidant activities.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in agreement with Kim et al. that showed that protein hydrolysate reduces the oxidative stress in vivo and increase the antioxidant activities.…”
Section: Discussionsupporting
confidence: 94%
“…This normalization is seen as an adaptation process, to face the oxidative stress by preventing the free radical production, so inhibiting the atherosclerosis development. Our results are in agreement with Kim et al [11] that showed that protein hydrolysate reduces the oxidative stress in vivo and increase the antioxidant activities.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Many nutritional intervention studies have showed that food-derived proteins or hydrolysates can reduce body weight and fat mass, and lower plasma cholesterol and triglycerides. Such as, proteins of white lupin seed were reported to reduce cholesterolemia in rats [2]; germinated soy protein hydrolysates had inhibitory effect on lipid storage and stimulating activity on lipolysis in 3T3-L1 cells [3]; yeast hydrolysate suppressed body fat accumulation by attenuating fatty acid synthesis in high-fat-diet-induced obese mice [4]; dietary fish protein hydrolysates were found to influence serum lipids and postprandial glucose regulation in obese Zucker fa/fa rats [5]; enzymatic hydrolysate from velvet antler significantly reduced the body weight gain, lowered the serum glucose and triglyceride levels in high-fat diet-fed mice [6]; yellow catfish protein hydrolysate displayed anti-obesity effects in high-fat diet fed mice, compared with those of mice treated with simvastatin [7]. The potential anti-obesity mechanisms include appetite regulation, lipid digestion/absorption intervention, fatty acid oxidation, regulation of lipogenesis and lipolysis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, fish hydrolysates have aroused enormous interests for their inexhaustible feature and high nutritional value [ 19 , 20 ]. Bioactive peptides with antimicrobial, antioxidant, anti-obesity, antihypertensive and cryoprotective effects from fish proteins in muscle, skin and even waste products have been reported [ 19 , 21 , 22 , 23 ]. Characterization of AHTPs in fish protein hydrolysates have been conducted in various species, such as salmon, tuna, grass carp and dace [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%